As contribuições da ecopedagogia musical para a ecoformação cidadã: uma experiência com o coral Verdes Vozes em Fortaleza - CE - Rocha, Ana Cléria Soares da (2016)
In recent years, the environment has been the common theme in many discussions in various areas including schools, universities, government institutions and NGOs. The study's contributions Musical ecopedagogy for eco-formation: An experience with the Choir Green Voices in Fortaleza-CE invites the following question: How does ecopedagogy can contribute to the use of music for an eco-formation? The overall objective: To demonstrate the possibility of using music as ecological awareness strategy by ecopedagogy. The motivation for this study relied on work in education, focused on the teaching of music and for teaching environmental education. The field research with qualitative and quantitative approach was to subject the Choir Green Voices components in the city of Fortaleza, in the period between August 2013 to December 2014. And the data collection was conducted through semi-structured interview on the occasion of events held with the choir. The theoretical contributions were based on the socio-cultural theory of Vygotsky (1996), in rhythmic theory Dalcroze (1930), discussed by Fonterrada (2008), the Bridging approach de Oliveira (2006) and still in the learning theory of Ausubel (2008). The survey showed through the coral role that music constitutes an ecological awareness strategy by ecopedagogy for civic education. It was found that there is still a long way to go to make this happen ecological awareness